The Epstein-Barr virus B-ZIP protein Zta recognizes specific DNA sequences containing 5-methylcytosine and 5-hydroxymethylcytosine - Tillo, Desiree (Biochemistry, 2017)
The Epstein-Barr virus (EBV) B-ZIP transcription factor (TF) Zta binds to many DNA sequences containing methylated CG dinucleotides. Using protein binding microarrays (PBMs), we analyzed the sequence specific DNA binding of Zta to four kinds of double-stranded DNA (dsDNA): 1) DNA containing cytosine in both strands, 2) DNA with 5-methylcytosine (5mC) in one strand and cytosine in the second strand, 3) DNA with 5-hydroxymethylcytosine (5hmC) in one strand and cytosine in the second strand, and 4) DNA where both cytosines in all CG dinucleotides contain 5mC. We compared these data to PBM data for three additional B-ZIP proteins (CREB1 and CEBPB homodimers, and cJun|cFos heterodimers). With cytosine, Zta binds the TRE motif TGA(C)/(G)TCA as previously reported. With CG dinucleotides containing 5mC on both strands, many TRE motif variants containing a methylated CG dinucleotide at two positions in the motif, such as MGAGTCA and TGAGMGA (where M=5mC) were preferentially bound. 5mC inhibits Zta binding to both TRE motif half sites GTCA and CTCA. Like the CREB1 homodimer, the Zta homodimer and the cJun|cFos heterodimer bind the C/EBP half site tetranucleotide GCAA stronger when it contains 5mC. Zta also binds dsDNA sequences containing 5hmC in one strand, although the effect is less dramatic than observed for 5mC. Our results identify new DNA sequences that are well-bound by the viral B-ZIP protein Zta only when they contain 5mC or 5hmC, uncovering the potential for discovery of new viral and host regulatory programs controlled by EBV.